(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the research work, the results of taxable samples of mining serum of 205 children in 16 family polyclinics were used. In a retrospective population taxile using epidemiological, serological, statistical methods, the effectiveness of the vaccine against SARS-CoV-2 was evaluated. 7,158 of the 584,181 children living in Tashkent City were vaccinated with 2 doses of the vaccine, 205 children in 16 family polyclinics where the vaccine was carried out were taught karshi IgG to SARS-CoV-2 and anti-cancer (at) belonging to IgM class. The verification process was carried out using a full-fledged automated chemiluminescent immunoanalyzer (medical equipment from Snibe (China)) of the MAGLUMI X3 series in an immunoxemiluminescent taxile (IXLT) method.